Analysis Of Preferences Factors Influencing Consumer Decision Making In Purchasing Ornamental Fish (Study at The Center For Ornamental Fish Promotion, Bekasi City, West Java - hasna fadilah lestari; Sulistyo Sidik Purnomo; Kuswarini Sulandjari (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2023)
Ornamental fish is one of the commodities that are in demand by the public, especially in urban areas. Ornamental fishmongers need to pay attention to the tastes of consumers in order to maintain and increase their sales turnover. This study is aimed at: identifying consumer characteristics, analyzing consumer preferences in buying ornamental fish, analyzing the factors of that influence consumer decision making in the purchase of ornamental fish at the Bekasi City Ornamental Fish Promotion Center. This study used primary dor primary taken by interview technique using questionnaires. Accidental sampling of 100 ornamental fish consumers. Secondary data were obtained from the relevant agencies in this study, namely data from BPS and literature studies. Analysis techniques used: Likert scale, descriptive, and multiple linear regression. The results of the study: Ornamental fish consumers are dominated by men with an age range of 22 years to 28 years, the final education level of Bachelor (S1) work is dominated by Private Employees, and the income level is Rp.2,500.000 - Rp. 5,000,000/month; Consumer preferences are influenced by the color and pattern of ornamental fish, the purpose of buying for entertainment or hobbies, the type of ornamental that is most in demand is chana, the frequency of purchases per consumer is an average of 2-3 heads, the purchase is dominated by buying different types of fish and aquarium equipment , friend as information, reasons for buying and satisfaction, namely the variety and availability of fish species; Simultaneously factors: cultural, social, personal, psychology have a significant influence on purchasing decisions. Partially personal factors (X3) and factors of psychology (X4) have a marked effect on consumer decision-making in the purchase of ornamental fish with koefisien positive. Fcultural actors (X1), and social factors (X2) have no real effect on the purchasing decision of ornamental fish.